Writing your journal article in twelve weeks a guide to academic publishing success - Belcher, Wendy Laura (Chicago guides to writing, editing, and publishing., 2019)
"Wow. No one ever told me this!" Wendy Laura Belcher has heard this countless times throughout her years of teaching and advising academics on how to write journal articles. Scholars know they must publish, but few have been told how to do so. So Belcher made it her mission to demystify the writing process. The result was Writing Your Journal Article in Twelve Weeks, which takes this overwhelming task and breaks it into small, manageable steps. For the past decade, this guide has been the go-to source for those creating articles for peer-reviewed journals. It has enabled thousands to overcome their anxieties and produce the publications that are essential to succeeding in their fields. With this new edition, Belcher expands her advice to reach beginning scholars in even more disciplines. She builds on feedback from professors and graduate students who have successfully used the workbook to complete their articles. A new chapter addresses scholars who are writing from scratch. This edition also includes more targeted exercises and checklists, as well as the latest research on productivity and scholarly writing. Writing Your Journal Article in Twelve Weeks is the only reference to combine expert guidance with a step-by-step workbook. Each week, readers learn a feature of strong articles and work on revising theirs accordingly. Every day is mapped out, taking the guesswork and worry out of writing. There are tasks, templates, and reminders. At the end of twelve weeks, graduate students, recent PhDs, postdoctoral fellows, adjunct instructors, junior faculty, and international faculty will feel confident they know that the rules of academic publishing and have the tools they need to succeed.